Secondary Syphilis in Human Immunodeficiency Virus (HIV)-Infected Men Who Have Sex with Men (MSM): A Case Report - Ade Fernandes; Evy Ervianti (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Recently, the incidence of syphilis among men who have sex with men (MSM) has increased rapidly, especially among Human Immunodeficiency Virus (HIV)-infected MSM. Coinfection with these two organisms alter the symptoms and signs, progression of the disease, and the risk of progressing to the tertiary stage. Purpose: To report a case of secondary syphilis in HIV-infected MSM. Case: A 24-year-old male complaint of multiple redness macule for 1-month duration on his chest, back, groin, palm, and soles. The rash was neither painful nor pruritic. He also complains of hair loss resulting